A novel microscopic method for analyzing gram-stained vaginal smears in the diagnosis of disorders of vaginal microflora - Nenadić Dane B.; Pavlović Miloš D.; Motrenko Tatjana (Vojnosanitetski Pregled)
Background/Aim. The Nugent’s score is still the gold standard in the great majority of studies dealing with the assessment of vaginal flora and the diagnosis of bacterial vaginosis (BV). The aim of this study was to show that the analysis of Gram-stained vaginal samples under microscope at the magnification of ×200 (a novel microscopic method - NMM), as a fast and simple tool, easily applicable in everyday practice, better reflects complexity of vaginal microflora than the Nugent’s methodology (×1000). Methods. Gramstained vaginal smears from 394 asymptomatic pregnant women (24-28 week of pregnancy) were classified according to the Nugent’s microscopic criteria (immersion, magnification ×1000). The smears were then reexamined under immersion but at magnification ×200. All samples were classified into 6 groups according to semiquanititative assessment of numbers (cellularity) and the ratio of rod (length < 1.5 μm) and small bacterial (< 1.5 μm) forms: hypercellular (normal full - NF), moderately cellular (normal mid - NM), hypocellular (normal empty - NE), bacterial vaginosis full (BVF), bacterial vaginosis mid (BVM), and bacterial vaginosis empty (BVE). Also yeasts, coccae, bifido and lepto bacterial forms as well polymorphonuclear (PMN) leukocytes were identified. Results. According to the Nugent’s scoring, BV was found in 78, intermediate findings in 63, and yeasts in 48 patients. By our criteria BV was confirmed in 88 patients (37 BVF, 24 BVM, and 27 BVN). Generally, both tools proved to be highly concordant for the diagnosis of BV (Lin’s concordance correlation coefficient = 0.9852). In 40% of the women mixed flora was found: yeasts in 126 (32%), coccae in 145 (37%), bifido forms in 32 (8%) and lepto forms in 20 (5%). Almost a half of BV patients had also yeasts (39/88). Elevated PMN numbers were found in 102 (33%) patients with normal and in 36 (41%) women with BV. Conclusion. The newly described methodology is simpler to apply and much better reflects diversity of vaginal microflora. In this way it may be more valuable to molecular biologists and their attempts based on quantitative polymerase chain reaction (PCR) to define formulas for molecular diagnosis of bacterial vaginosis.